Tissue Factor Pathway Inhibitor‐2 Silencing Promotes Hepatocellular Carcinoma Cell Invasion In Vitro. Issue 11 (24th October 2013) - Zhu, Bin; Zhang, Ping; Zeng, Ping; Huang, Zhen; Dong, Ting‐Fang; Gui, Yong‐Kun; Zhang, Guang‐Wen
ABSTRACT Hepatocellular carcinoma (HCC) is a leading cause of cancer‐related death in the world and metastasis is an essential aspect of HCC progression. Tissue factor pathway inhibitor‐2 (TFPI‐2) has been implicated as a potential suppressor gene to regulate tumor invasion and metastasis. In this study, we silenced TFPI‐2 in the HCC cell line MHCC97‐L and evaluated the role of TFPI‐2 in cell invasion and its impact on gene expression. We showed in this study that stable TFPI‐2 downregulation in MHCC97‐L cells resulted in increased cell adhesion and invasion. We also showed that mRNA and protein expression levels of MMP‐1/3, CD44, and ICAM‐1 were increased, while those of MMP‐2/9 were not changed by TFPI‐2 silencing. Furthermore, silencing of TFPI‐2 caused increased Akt phosphorylation level and NF‐κB transcription in MHCC97‐L cells. In conclusion, this study confirms that TFPI‐2 downregulation can contribute to tumor invasion of HCC cells through alteration in the expression of metastasis‐related genes. Anat Rec, 296:1708–1716, 2013. © 2013 Wiley Periodicals, Inc.